A sustentabilidade da reforma educacional em questão: a posição dos organismos internacionais - Nora Krawczyk (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2002)
This article discusses the themes and questions dealt with in the productions of international organisations from 1998 onwards with relation to different dimensions of the sustainability of the educational reforms in Latin America which offer interesting signs of those aspects which have and will continue to receive technical and financial investments from such organisations. At least three dimensions concern the international organisations: the political, the financial and the technical dimensions. This analysis is based on an examination of publications by the World Bank, CEPAL, PREAL, BID, IIPE/ UNESCO and OREALC/UNESCO, from 1998 to 2001.